Allogeneic haematopoietic cell transplantation for adult acute myeloid leukaemia in second remission: a retrospective study of the Adult Acute Myeloid Leukaemia Working Group of the Japan Society for Haematopoietic Cell Transplantation (JSHCT). (29th May 2018) - Konuma, Takaaki; Yanada, Masamitsu; Yamasaki, Satoshi; Kuwatsuka, Yachiyo; Fukuda, Takahiro; Kobayashi, Takeshi; Ozawa, Yukiyasu; Uchida, Naoyuki; Ota, Shuichi; Hoshino, Takumi; Takahashi, Satoshi; Kanda, Yoshinobu; et al.
Summary: To evaluate the outcomes and prognostic factors following allogeneic haematopoietic cell transplantation (HCT) for adult acute myeloid leukaemia (AML) in second complete remission (CR2), we retrospectively analysed the Japanese registration data of 1080 adult AML patients in CR2 who had received allogeneic HCT. The probability of overall survival and the cumulative incidence of relapse at 3 years was 66% and 19%, respectively. In multivariate analysis, older age, poor cytogenetics and shorter duration of first complete remission were significantly associated with a higher overall mortality. Our data demonstrated the significant efficacy of allogeneic HCT for adult AML in CR2.